2010
DOI: 10.1253/circj.cj-10-1012
|View full text |Cite
|
Sign up to set email alerts
|

Is Angioplasty Able to Become the Gold Standard of Treatment Beyond Bypass Surgery for Patients With Multivessel Coronary Artery Disease? - Therapeutic Strategies for 3-Vessel Coronary Artery Disease: OPCAB vs PCI (PCI-Side) -

Abstract: The optimal strategy of revascularization for multivessel disease has been controversial for a long time. In general, the initial trials 1-5 performed in the 1990s to compare PCI and CABG enrolled patients who had relatively low risk and relatively normal left ventricular function. Study participants primarily had 2-vessel disease that was deemed treatable by either method, and none had serious comorbid conditions. Those trials were performed before widespread use of coronary stents and glycoprotein IIb/IIIa i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…12,13) Hybrid revascularization combines minimally invasive coronary artery bypass, such as ThoraCAB and totally endoscopic CABG, with PCI; integrating these two procedures into one therapeutic modality aims to provide patients with the benefits of each successive technique in the least invasive way. The survival benefit of the left IMA for ostial or complex lesions of the LAD has been established.…”
Section: Hybrid Proceduresmentioning
confidence: 99%
“…12,13) Hybrid revascularization combines minimally invasive coronary artery bypass, such as ThoraCAB and totally endoscopic CABG, with PCI; integrating these two procedures into one therapeutic modality aims to provide patients with the benefits of each successive technique in the least invasive way. The survival benefit of the left IMA for ostial or complex lesions of the LAD has been established.…”
Section: Hybrid Proceduresmentioning
confidence: 99%
“…In this regard, PCI vs. CABG for MVD in the current DES era is to be further tested. 20 The superiority of DES itself, in terms of safety, seems to be challenging. Among reports comparing the safety of DES vs. BMS, a few observational studies and their meta-analysis reported even better safety for using DES.…”
Section: Chung Jw Et Almentioning
confidence: 99%
“…Regarding the issue of individualized treatment selection, a subgroup analysis that pooled individual patient data suggested that CABG might be better for patients with DM and for those aged 65 years or older. 31- 33 That result indicates that a better coronary revascularization strategy is possible in theory if individual risk profiles are taken into account.…”
Section: Can Prediction Models For Mortality After Pci and Cagb Be Usmentioning
confidence: 99%